Pb-Pb zircon ages for tourmaline alkali-feldspar orthogneiss from Hluboka nad Vltavou in southern Bohemia - Vrana,S.; Kroner,A. (Journal of the Czech Geological Society, 1995)
The pre-Variscan tourmaline-bearing orthogneiss occurring near Hluboka nad Vltavou is tectonically intercalated in sillimanite-biotite paragneisses of the Monotonous Unit of the Moldanubian Zone and is a metamorphosed biotite-muscovite alkali-feldspar granite with a composition comparable to pegmatite. Zircons from a sample of this orthogneiss were dated by single grain evaporation and yielded a mean 207Pb/ 206Pb age of 508 &#177 7 Ma, interpreted to approximate the time of granite emplacement. One xenocrystic zircon grain with a 207Pb/ 206Pb age of 606 &#177 8 Ma either suggests derivation of the granite by anatexis from a late Precambrian crustal source or digestion of such material during ascent and/or emplacement of the granite. The emplacement age is similar to zircon ages for granitoid gneisses exposed in the Orlicke hory Mts. and Sneznik Dome and may suggest that Ordovician granitoid activity was widespread in southern a eastern Bohemian Massif.
Keywords: Pb-Pb zircon ages; tourmaline alkali-feldspar orthogneiss; southern Bohemia; Moldanubian Zone